Analisis Dampak Perkembangan Teknologi 4.0 Pada Perilaku Masyarakat Melalui Pendekatan Komunikasi Massa - Annisa Weriframayeni; Yolanda Oktarina; Syahrul Ramadhan (Peneliti.net, 2022)
This study aims to analyze the impact of technological developments 4.0. The most rapid technological development was at the time of the emergence of the Industrial Revolution 4.0 era where machines, software and other sophisticated tools began to be created to help facilitate human work in carrying out activities, as well as increase productivity in the digital world very quickly.